SHORT-TERM PRESERVATION OF BRACH/ONUS CALYCIFLORUS: EFFECTS OF STORAGE ON PROTEIN, LIPID AND CARBOHYDRATE CONTENTS - Srivastava, Punit K.; Roy, D. (Journal of Indian Fisheries Association, 2007)
The short-term preservation of Brachionus calycijlorus for 45 days at three different temperatures ( 4, -4 and -20°C) led to decrease in protein, lipid and carbohydrate contents in all the three cases. However, the rate of deterioration was much higher at 4C than at -4 and -20°C. At 4C, protein, lipid and carbohydrate contents reduced by 76. 78, 81.11 and 62.83 °/o, respectively, and at -4°C, these were 27.94, 37.46 and 18.42°/o, respectively, whereas at -20°C, the deterioration was limited to 9.28, 16.44 and 11.35%, respectively, when compared with the control values. Thus, preservation at -20°C is comparatively better as it exerts limited effect on the protein, lipid and carbohydrate contents of B. calycijlorus. Keywords: Preservation, Brachionus calycijlorus, protein,carbohydrate, lipid